2017
DOI: 10.1016/j.addbeh.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Medical and nonmedical use of prescription sedatives and anxiolytics: Adolescents' use and substance use disorder symptoms in adulthood

Abstract: Objectives This study assessed the longitudinal associations between medical and nonmedical use of prescription sedatives/anxiolytics (NMPSA) during adolescence (age 18) and substance use disorder (SUD) symptoms during adulthood (age 35). Methods Multiple cohorts of nationally representative samples of U.S. high school seniors (n = 8,373) were surveyed via self-administered questionnaires and followed longitudinally from adolescence (age 18, 1976–1996) to adulthood (age 35, 1993–2013). Results An estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 40 publications
5
25
0
Order By: Relevance
“…Past-year tranquilizer/sedative misuse was most likely in young adults, at 5.8%; 42.8% of all young adults engaged in past-year use also engaged in past-year misuse. Similar results were found in 18 year-old participants in the nationally-representative Monitoring the Future survey, with 44.9% of those with lifetime medical tranquilizer/sedative use also engaged in nonmedical misuse (McCabe, Veliz, Boyd, & Schulenberg, 2017). Young adults also had the highest rates of past-month misuse.…”
Section: Discussionsupporting
confidence: 68%
“…Past-year tranquilizer/sedative misuse was most likely in young adults, at 5.8%; 42.8% of all young adults engaged in past-year use also engaged in past-year misuse. Similar results were found in 18 year-old participants in the nationally-representative Monitoring the Future survey, with 44.9% of those with lifetime medical tranquilizer/sedative use also engaged in nonmedical misuse (McCabe, Veliz, Boyd, & Schulenberg, 2017). Young adults also had the highest rates of past-month misuse.…”
Section: Discussionsupporting
confidence: 68%
“…Schepis and Krishnan-Sarin (2009) found that adolescent nonmedical misusers had higher rates of other substance use and frequent PDM than medical misusers. Adolescent nonmedical opioid and stimulant misusers also have higher rates of SUD symptoms in adulthood (McCabe et al, 2017; McCabe et al, 2016). However, medical misuse is associated with poorer outcomes than nonmedical misuse, depending on underlying motives (McCabe et al, 2013), and even medical use can impart risk, as adolescent opioid users have higher follow-up opioid-PDM rates than non-users (McCabe et al, 2016; Miech et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Significant cross-sectional evidence links PDM and psychopathology in adults 5,6 and adolescents, 7 with prospective evidence associating adult PDM with incidence and recurrence of major depression (MDD), generalized anxiety and panic disorder at a three-year follow-up. 8 Adolescent PDM also co-occurs with substance use disorder (SUD) development in adulthood, 9 poorer adult educational outcomes 10 and other poor psychosocial outcomes (e.g., aggressive behavior). 11 The most commonly misused medication class was opioids (3.5%), with roughly half as many adolescents (1.7% each) engaged in prescription stimulant or tranquilizer (a term capturing primarily benzodiazepine medication) misuse.…”
Section: Introductionmentioning
confidence: 99%
“…13 Longitudinal evidence links PDM initiation during adolescence with greater risk of PDMrelated SUD symptoms and lower educational attainment in adulthood. 9,10,14 Given the consequences of adolescent PDM, limiting it is a worthy public health goal.…”
Section: Introductionmentioning
confidence: 99%